A Comparison of Fine Needle Aspiration Biopsy and Excisional Biopsy Results in the Diagnosis of Lymphoma Confined to the Head and Neck Region - Özlem Önerci Çelebi; Yusuf Muhammed Durna; Deniz Tuna Edizer; Özgür Yiğit; Yeşim Karagöz; Gülben Erdem Huq (İstanbul Medical Journal, 2016)

(untitled)
Objective: To compare fine needle aspiration biopsy (FNAB) and excisional biopsy results in the diagnosis of head and neck lymphomas and to evaluate the effectiveness of FNAB.Methods: The medical files of 52 patients diagnosed with lymphoma in our clinic between September 2011 and January 2015 were retrospectively examined. Demographic characteristics, presenting complaints, hematologic parameters, fine needle aspiration biopsy (FNAB) results, and excisional biopsy results of the patients were recorded. The patients were divided into 4 groups based on their FNAB cytology results: i) malignant cytology, ii) suspicious for lymphoid neoplasia, iii) mixed lymphoid cell population, and iv) non-diagnostic cytology. FNAB was performed under ultrasound guidance.Results: The average age within our series, which consisted of 37 male and 15 female patients, was 46.37 (range 8–82 years). Neck mass was the presenting symptom in 30 patients (57.6%), while it was detected during examination of other symptoms in 22 patients (42.3%). Fever was not observed in any of the patients, whereas weight loss was present in 12 patients (23%), fatigue in 5 patients (9.6%), and night sweats in 5 patients (9.6%). Following excisional biopsy, Hodgkin lymphoma was diagnosed in 28 patients and non-Hodgkin lymphoma was diagnosed in 24 patients.Conclusion: The utility of FNAB in the diagnosis of lymphoma in the head and neck region is discussed. FNAB may not be sufficient unless immunofluorescence examination is also conducted. FNAB may lead to a considerable delay in establishing a definitive diagnosis. In the case of clinical suspicion, excisional biopsy is recommended without performing FNAB.